REGULATION OF MAXIMUM TARIFF OF FLIGHT TICKETS FOR ECONOMIC CLASS PASSANGERS IN INDONESIA - Isrami Yuristiana, Gita; Sudiro, Amad (Transnational Business Law Journal, 2020)
Minister of Transportation Decree No. 106 of 2019 is a government reaction to soaring flight ticket fare on domestic routes. This Minister Decree aims to prevent unfair business competition practices as mandated by Law No. 5 of 1999. On the other hand, Law No. 5 of 1999 itself does not provide an explanation of what kind of price fixing referred to by Article 5 of the Act. This then raises a question regarding business competition between business actors. This legal issue starts from the most basic condition whether the airline have carried out the sale of airline tickets that do not harm passengers, and of course there is a legal basis. The society's need for air transportation is increasing every year, but is constrained by the increasingly expensive airline ticket rates. The society and business actors need the role of the government to be able to make policies that are impartial while still considering the interests of the society and business doers.